2007
DOI: 10.1002/nau.20527
|View full text |Cite
|
Sign up to set email alerts
|

Should we explain lower urinary tract symptoms to patients?

Abstract: Our findings showed that most women do not know the correct meaning of LUTS terminology currently used by physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…Thus, an advantage of the LUTS Tool is its use of non‐medical terminology. Digesu et al22 explored the percentage of women who could correctly define LUTS symptoms and found that patient understanding of these terms was suboptimal for accurate diagnoses. By comparison, the LUTS Tool was developed using qualitative data from both men and women with LUTS, mimicking the phrases and terms used by LUTS patients to describe their symptom frequency and bother 14.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an advantage of the LUTS Tool is its use of non‐medical terminology. Digesu et al22 explored the percentage of women who could correctly define LUTS symptoms and found that patient understanding of these terms was suboptimal for accurate diagnoses. By comparison, the LUTS Tool was developed using qualitative data from both men and women with LUTS, mimicking the phrases and terms used by LUTS patients to describe their symptom frequency and bother 14.…”
Section: Discussionmentioning
confidence: 99%
“…34 In a study of 2737 women with UI symptoms, 1626 (59%) reported mixed UI, of whom 42% had USI, 25% had pure DO, 18% had both DO and USI and 15% had normal UDS. 35 In those with stress-predominant MUI, 64% had pure USI and in those with urgency-predominant MUI, only 47% had solely DO.…”
Section: Urodynamicsmentioning
confidence: 94%
“…8 We clearly need a better insight into the sensation of urgency that we are talking about, and furthermore find a clear description understandable by patients at the 6th grade level. Before we can fine tune the definition, some issues should be addressed: should we demarcate sudden and gradual urgency, should we differentiate by perceived cause of urgency and can we use definitions to stratify patients by clinical condition?…”
Section: Abstract: Afferent; Sensation; Urgencymentioning
confidence: 99%